Seismic behavior and modeling of steel reinforced concrete (SRC) walls. (24th October 2014) - Ji, Xiaodong; Sun, Ya; Qian, Jiaru; Lu, Xinzheng
Summary The steel reinforced concrete (SRC) wall consists of structural steel embedded at the boundary elements of a reinforced concrete (RC) wall. The use of SRC walls has gained popularity in the construction of high‐rise buildings because of their superior performance over conventional RC walls. This paper presents a series of quasi‐static tests used to examine the behavior of SRC walls subjected to high axial force and lateral cyclic loading. The SRC wall specimens showed increased flexural strength and deformation capacity relative to their RC wall counterpart. The flexural strength of SRC walls was found to increase with increasing area ratio of embedded structural steel, while the section type of embedded steel did not affect the wall's strength. The SRC walls under high axial force ratio had an ultimate lateral drift ratio of approximately 1.4%. In addition, a multi‐layer shell element model was developed for the SRC walls and was implemented in the OpenSees program. The numerical model was validated through comparison with the test data. The model was able to predict the lateral stiffness, strength and deformation capacities of SRC walls with a reasonable level of accuracy. Finally, a number of issues for the design of SRC walls are discussed, along with a collection and analysis of the test data, including (1) evaluation of flexural strength, (2) calculation of effective flexural stiffness, and (3) inelastic deformation capacity of SRC walls. Copyright © 2014 John Wiley & Sons, Ltd.